Physiological parameters and nutrient uptake in unpuddled machine transplanted rice (Oryza sativa) in combination with alternative wetting and drying - S, SELVAKUMAR; K, SHOBAN CHAKRAVARTHY; KUMAR, AJAY (The Indian Journal of Agricultural Sciences, 2024)
A field study was carried out during rabi (winter) seasons of 2018–19 and 2019–20 at Agricultural College and Research Institute, Tamil Nadu Agricultural University, Madurai, Tamil Nadu to study the effect of four different crop establishment methods, viz. manual transplanting; transplanting of rice seedling in puddled soil using machine; transplanting of rice seedling in non-puddled soil using machine; and direct sowing combined with four different irrigation treatments, viz. farmers practice; irrigation following the development of a hairline crack; irrigation when water level descents 5 cm; and 10 cm below soil surface on physiology of rice (Oryza sativa L.). Experiment was conducted in a strip plot design replicated thrice. The study revealed that nutrient uptake and physiological parameters were found to be maximum with seedlings of rice crop transplanted in non-puddled soil using machine combined with irrigation following the development of a hairline crack. Seedlings of rice crop transplanted in non-puddled soil using machine combined with irrigation once the water level descends to 5 cm beneath the soil surface, had a significant positive influence on rice yield during both the years. It also recorded higher photosynthetic rate and improved physiological parameters, and yield even with minimum use of water. So, it may be recommended as the best alternate method of rice cultivation compared to conventional method where the rainfall is deficit.